Determinan Kejadian Obesitas Sentral pada Wanita Usia Subur (15-49) Tahun di Indonesia : (Analisis Data SKI Tahun 2023) - Putri Vira Nanda; Adelina Fitri; Muhammad Syukri; Ismi Nurwaqiah Ibnu; Marta Butar Butar (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Central obesity in women of reproductive age can have a negative impact on their health and is associated with the occurrence of metabolic diseases. This study aims to determine the factors associated with central obesity in women aged 15-49 years in Indonesia in 2023 using 2023 SKI data with a cross-sectional study design. The study sample was 213,309 women of reproductive age obtained using the linear systematic sampling technique. Data analysis was carried out up to multivariate analysis using the Cox Regression test. The results showed that the prevalence of central obesity in women of reproductive age was 49.11%. Age [PR = 1.96 (95% CI: 1.93 - 2.00)], occupation [PR = 1.20 (95% CI: 1.19 - 1.22)], and place of residence [PR = 1.08 (95% CI: 1.07 - 1.10)] were found to be associated with an increased risk of central obesity. Meanwhile, education level [PR = 0.97 (95% CI: 0.95 – 0.98)], physical activity [PR = 0.93 (95% CI: 0.91 – 0.94)], and emotional mental disorders [PR = 0.75 (95% CI: 0.70 – 0.80)] were found to be protective factors against central obesity. The most dominant factor with the occurrence of central obesity is age. Therefore, it is important for WUS to be aware of the risk of central obesity and implement appropriate preventive measures. Preventive efforts can be done by maintaining hormonal balance and body metabolism through a healthy lifestyle, as well as undergoing regular health checks.